Glycemic Control in Type 2 Diabetes Mellitus Patients Could Affect NLRP3 Inflammasome Level - Refif Sabih Al-Shawk; Zainab Fadhel Ashoor; Wasan Abdul-elah Bakir; Intisar Manfi Ahmed (Medical Journal of Babylon)
Background: Inflammasome complex such as nucleotide oligomerization domain-like receptor family protein 3 (NLRP3) acts as a trigger initiating inflammatory responses and could lead to endothelial dysfunction in diabetic patients and glycemic control could affect the mitochondrial stress through NLRP3 inflammasome level. Objectives: This study was conducted to ensure that type 2 diabetes mellitus (T2DM) glycemic control could affect mitochondrial stress through NLRP3 inflammasome level leading to an aberrant immune response. Materials and Methods: A case–control study was conducted on 90 Iraqi subjects, 60 of them were T2DM who were subgrouped into 30 patients with good glycemic control (HbA1c ≤ 7%) and the second group with 30 patients with poor (bad) glycemic control (HbA1c > 7%). Also, 30 healthy control subjects were enrolled in this study. HbA1c, fasting blood glucose (FBG), and serum levels of NLRP3 and interferon (IFN)-γ were quantitatively determined by means of a sandwich enzyme-linked immunosorbent assay (ELISA) test. Results: Results of this study showed a significant increase in serum levels of NLRP3 and IFN-γ in the poor glycemic control group of patients as compared to control subjects (P ≤ 0.05), while this difference was not significant when comparing the good glycemic control group of patients with control subjects. There is a significant positive correlation of serum NLRP3 with only IFN-γ (P ≤ 0.05) in both good and poor glycemic control and healthy controls. Conclusion: An increased level of NLRP3 was observed in poor glycemic control T2DM and correlated with IFN-γ, suggesting hyperglycemia’s effect on this inflammasome pathway that could be associated with aberrant cytokine induction, a key inducer of diabetic complications.